EDUCATING SPECIALISTS IN LIBRARY FIELD IN TERMS OF SOCIETY INFORMATIZATION - Karakoz, Olena O. (University Library at a New Stage of Social Communications Development. Conference Proceedings, 2019)
The basic principles are considered of educating specialists in library field in terms of society informatization. The modern concept of modernization of higher library education are dealed and analyzed. Current trends of semantic and organizational foundations of higher library education are presented. Problems of professional and practical training of university students are revealed. Factors increasing the level of training highly qualified and competitive professionals for consumers of library branch are determined